PENYULUHAN PENGELOLAAN DAN PENGOLAHAN SAMPAH DI SDN KUDANGUYAH KOTA TASIKMALAYA - Saeful Karim Zaelani; Putri Jihan Afifah; Andini Aini Sukma; Hilmy Hazimatul Maishan; Jihad Fathulloh; Bayu Adi Laksono (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Waste is a result of production activities from both industry and household activities that are discarded as unused materials. The issue of waste has become a very important and well-known issue among the entire population. The increasing population and more complex human activities further exacerbate the waste problem. Unfortunately, this does not affect people's awareness and the lack of public effort to maintain a clean environment and avoid indiscriminate waste disposal. This location of the community service is located at SDN Kudanguyah in Tasikmalaya, West Java, with a method of socialization. The results of the activity are divided into three parts: planning, which contains activities to identify needs and understanding of the waste bank. The second part is the implementation of activities, which contains technical waste management activities. The third part is the evaluation, which contains activities that record problems that occurred during the implementation of the activity. The conclusion is that the waste management socialization activity is considered successful with increased enthusiasm from the targets in the implementation of the activity and the follow-up after the activity which will actually implement the waste bank in waste management in the target area.